No difference in postprandial mesenteric blood flow between healthy younger and elderly individuals - Thomas Hartwig Siebner; Jens Dahlgaard Hove; Christopher Fugl Madelung; Oliver James Hulme; Flemming Bendtsen; Hartwig Roman Siebner; Mads Barløse (Scientific Reports, 2024)
Abstract We recently used phase-contrast magnetic resonance imaging (PC-MRI) to demonstrate an attenuated postprandial blood flow response in the superior mesenteric artery (SMA) in patients with Parkinson's disease compared to age- and sex-matched healthy controls. Since both groups showed substantial inter-individual variations, we extended the cohort of controls with a group of young individuals to investigate possible age-related effects. Seventeen healthy young subjects aged < 30 years and 17 elderly subjects aged > 50 years underwent serial PC-MRI to measure the postprandial blood flow response in the SMA after ingestion of a standardized liquid test meal (∼400 kcal). Postprandial blood flow dynamics in SMA did not differ between young and elderly subjects. A noticeable inter-individual variation in postprandial intestinal blood flow increase was found, and approximately 30% of the variation could be explained by the preprandial blood flow. Regardless of age, some subjects showed a remarkable transient SMA blood flow increase immediately after meal intake. This study provides tentative evidence that postprandial blood flow dynamics in SMA in healthy young and elderly subjects do not substantially differ, indicating that age is without impact on vascular response in SMA as an indicator for regulation of mesenteric perfusion in response to food intake.